Design and characterization of swietenia mahagoni jacq. Mediated silver nanoparticles for hyperglycemic and hyperlipidemic control (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The present study was designed to evaluate the design and characterization of swieteniamahagonijacq. mediated silver nanoparticles for hyperglycemic and hyperlipidemiccontrol. Usingtheextraction methods like soxhlet extraction, benzene extraction, Ethanolic Extraction, Ethyl acetate extraction, petroleum ether extraction.Animals were randomly divided into 5 groups. Group 1- normal control, Group 2- diabetic control, Group3 –treatment control Swieteniamahagoni 100mg/kg, Group 4 – Swieteniamahagoni 200mg/kg treated group, Group 5 – Glibenclamide 5mg/kg.The levels of biochemical parameter, body weight, serum lipid profile, serum total cholesterol, serum glycerides, VLDL AND & HDL cholesterol, HDL cholesterol, Hemoglobin &glycatedhemoglobin were examined in each of these groups. Chronic administration of swieteniamahagoni at a dose of 100mg/kg & 200mg/kg, p.o. for a period of 21 days markedly decreased the level of blood glucose level & lipid level. Phamacological studies were assessed forbioassessment, clinical trials, and toxicological studies.  Quantitative estimation of total phenolic and flavonoid likeestimation of total phenolic content, total flavonoid content,HPTLC investigation of ethanol extract.Taken together, the results suggested that treatment reduced hyperglycemic and hyperlipidemic control. This study demonstrates the swieteniamahagonijacq.  Mediated silver nanoparticles for hyperglycemic and hyperlipidemic control.